2019
DOI: 10.1051/0004-6361/201935552
|View full text |Cite
|
Sign up to set email alerts
|

Transiting exocomets detected in broadband light by TESS in the β Pictoris system

Abstract: Aims. We search for signs of falling evaporating bodies (FEBs, also known as exocomets) in photometric time series obtained for β Pictoris after fitting and removing its δ Scuti-type pulsation frequencies.Methods. Using photometric data obtained by the TESS satellite we determined the pulsational properties of the exoplanet host star β Pictoris through frequency analysis. We then pre-whitened the 54 identified δ Scuti p-modes and investigated the residual photometric time series for the presence of FEBs. Resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 46 publications
12
74
0
1
Order By: Relevance
“…However, a moderate eccentricity would fit nicely in the dynamics of the system. An e ≈ 0.15 is consistent with the picture of an eccentric β Pic b launching small bodies towards the star, causing spectroscopic and transiting signatures of exocomets in observations of the star (Thébault & Beust 2001;Zieba et al 2019). An interesting question is how such a massive planet acquired a significant eccentricity.…”
Section: Orbital Parameterssupporting
confidence: 79%
“…However, a moderate eccentricity would fit nicely in the dynamics of the system. An e ≈ 0.15 is consistent with the picture of an eccentric β Pic b launching small bodies towards the star, causing spectroscopic and transiting signatures of exocomets in observations of the star (Thébault & Beust 2001;Zieba et al 2019). An interesting question is how such a massive planet acquired a significant eccentricity.…”
Section: Orbital Parameterssupporting
confidence: 79%
“…This study found that participants were exposed to trauma from the emergence of the COVID-19 outbreak in Indonesia. Inconsistent with some other studies (Siqveland et al, 2015;Zieba et al, 2019), trauma condition scores do not significantly affect the stress-related growth experienced by individuals. This is because the emergence of growth requires gradual cognitive processes and perceived traumatic experiences.…”
Section: Discussionsupporting
confidence: 75%
“…In the 51 Oph system, solid cometary material with a similar composition could have been converted to gaseous form from collisions or during close approaches toward the star. Such an outlook is consistent with the observations of transient absorption lines associated with falling evaporating bodies (FEBs) detected for 51 Oph and other stars with circumstellar disks (Vidal-Madjar et al 1994Beust et al 1998Beust et al , 2001Karmann et al 2001Karmann et al , 2003Thébault & Beust 2001 ;Roberge et al 2002 ;Beust & Valiron 2007 ;Welsh & Montgomery 2013 ;Kiefer et al 2014Kiefer et al , 2019Eiroa et al 2016 ;Vidal-Madjar et al 2017 ;Zieba et al 2019).…”
Section: Atomic Abundancessupporting
confidence: 80%